Effect of laparoscopic salpingectomy on subsequent ovarian response after controlled ovarian hyperstimulation - Yazbeck, Chadi; Boukadida, Asma; Chauvin, Christian; Margulies, Anne Laure; Falcone, Ségolène (Clinical Journal of Obstetrics and Gynecology, 2019)
Background: The effect of salpingectomy on ovarian response is a matter of debate. Due to conflicting data, alternative techniques were developed to perform salpingectomy for treatment of hydrosalpinges in infertile patients. This study aims to evaluate the effect of salpingectomy on ovarian response after stimulation with gonadotropins. Methods: In a retrospective analysis, one hundred fifty-seven patients with tubal infertility were divided into three groups according to their surgical histories: bilateral salpingectomy (BS group); unilateral salpingectomy (US group); and no history of salpingectomy (NS group). Ovarian response and IVF outcomes were compared between groups by analysis of variance. Prognostic factors for ovarian response were estimated by linear regression models. Results: In the BS group, the total numbers of oocytes retrieved, and embryos obtained were significantly lower than those in the NS group (p = 0.02). Poor ovarian response was also more frequent in the BS group (p = 0.02). In the US group, follicle development was reduced on the operated side. This effect was more pronounced when salpingectomies were performed for hydrosalpinges than when performed for ectopic pregnancies, and significant decreases were observed in follicle recruitment (p = 0.005) and oocyte retrieval (p = 0.02) on the operated side. Conclusion: Salpingectomy could have a minor negative effect on ovarian response. This is particularly true with bilateral salpingectomies, in which the ovarian blood supply could be disrupted, with no possible compensation by the contralateral side.